Access Means Inequality - Altbach, Philip (International Higher Education, 2010)
Expanding access would bring inequality to higher education. Institutions, while catering to unregulated mass access, provide vastly different quality, facilities, and focus than do elite institutions at the top, and this gulf has widened as access has expanded worldwide. Furthermore, mass higher education has, for a majority of students worldwide, lowered quality and increased dropout rates.